The card - Bennett, Arnold (Oxford University Press, 2008)
The Oxford Bookworms Library offers a variety of titles, many of which are touchstones of United States culture and history. Introductions lead students into the story. Illustrations support comprehension. Glossaries explain key topic words. Activities for Before, While, and After Reading help students reap maximum benefit. About the Author sections give students information about the author's life and work